Impact of various extra-oral factors on caries experience among mentally disabled children residing in Bhopal city, central India: A cross-sectional study - Sonal Chhajed (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2016)
Background: Dental caries is the most common dental problem among the mentally challenged children. There are various extra-oral factors responsible for high caries experience among such children. Aim: The aim of the present investigation was to study the impact of various extra-oral factors on dental caries experience among mentally challenged children residing in Bhopal city, Central India. Materials and Methods: One hundred and fifty-two children between the age group 5 and 15 years were included in this descriptive cross-sectional study. A pretested pro forma was used to record information about socioeconomic status, demographic data, mental retardation (MR) type, and intelligent quotient. The clinical examination was performed to evaluate dental caries and treatment needs using the World Health Organization dentition status and treatment needs index. Results: The mean decayed, missing, and filled teeth (DMFT and dmft) were 2.32 and 2.21, respectively. Age, parent occupation, income, and intelligent quotient were significant predictors of both DMFT and dmft. In addition, socio-economic status and type of MR were significant predictors of only DMFT. Conclusion: Dental health professionals should, therefore, be aware of the various extra-oral factors responsible for high caries experience of mentally challenged children. They should understand and provide basic treatment needs to such children.